Catheter-associated urinary tract infection: antimicrobial sensitivity profile* - Silvana Kelie Souza de Almeida Barros; Gilselena Kerbauy; Elma Mathias Dessunti (Rev Rene)
This descriptive quantitative study aimed to analyze the prevalence of microorganisms and the antimicrobial sensitivity profile from urine cultures of patients with catheter-associated urinary tract infection. We reviewed 394 medical records of adults hospitalized in the Intensive Care Units of the University Hospital of Londrina, Paraná, Brazil, from April to December 2011. The prevalence of catheter-associated urinary tract infection was of 34.0% (134) and 2.2% (3) of these patients developed sepsis. The most common microorganisms found in the urine cultures wereCandida sp (44.4%), Acinetobacter baumannii (9.7%) andPseudomonas aeruginosa (9.2%). This last one showed resistance of 86.7% to third-generation cephalosporins and the Acinetobacter baumannii showed resistance of 83.3% to carbapenems. Klebsiella pneumonia had 87.5% of resistance to third and fourth generation cephalosporins and 75.0% to carbapenems. We concluded that bacterial resistance is frequent in catheter-associated urinary tract infection and that we should emphasize the control measures.